"From the moment i wake up i will use it?every day, very hour": A qualitative study on the patterns of adolescents' mobile touch screen device use from adolescent and parent perspectives - Toh, S.; Howie, Erin; Coenen, P.; Straker, Leon (BioMed Central, 2019)
Background: The use of mobile touch screen devices, e.g. smartphones and tablet computers, has become increasingly prevalent among adolescents. However, little is known about how adolescents use these devices and potential influences on their use. Hence, this qualitative study explored adolescents' perceptions on their patterns of use and factors influencing use, and perceptions and concerns from parents. Methods: Semi-structured interviews were conducted with adolescents (n = 36; 11 to 18 years) and their parents/caregivers (n = 28) in Singapore recruited to represent males and females across a range of ages from different socioeconomic groups. Prompts covered weekday and weekend use patterns, types of activities, perspectives on amount of use, parental control measures and concerns. Interviews were recorded and transcribed. Transcripts were coded and thematic analysis was carried out. Results: Smartphone was the most common mobile device owned and used by many of the adolescents, while only some used a tablet. Many adolescents and their parents felt that adolescents' MTSD use was high, frequent and ubiquitous, with frequent checking of device and multitasking during use. Reported influences of use included functional, personal and external influences. Some of the influences were irresistibility of mobile devices, lack of self-control, entertainment or relaxation value, and high use by peers, family and for schoolwork that contributed to high use, or school/parental control measures and lack of internet availability that limited use. Most adolescents were generally unconcerned about their use and perceived their usage as appropriate, while most parents expressed several concerns about their adolescents' use and perceived their usage as excessive. Conclusions: This study has provided rich insights into the patterns and influences of contemporary mobile device use by adolescents. Mobile device use has become an integral part of adolescents' daily routines, and was affected by several functional, personal and external influences which either facilitated or limited their use. There also seemed to be a strong inclination for adolescents to frequently check and use their mobile devices. There is an urgent need to understand the implications of these common adolescent behaviours to inform advice for wise mobile device use by adolescents.